2020
DOI: 10.1101/2020.06.04.133603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleeping While Awake: The Intrusion of Neural Activity Associated with Sleep Onset in the Awake Human Brain

Abstract: Sleep can intrude into the awake human brain when sleep deprived or fatigued, even while performing cognitive tasks. However, how the brain activity associated with sleep onset can co-exist with the activity associated with cognition in the awake humans remains unexplored. Here, we used simultaneous fMRI and EEG to generate fMRI activity maps associated with EEG theta (4-7 Hz) activity associated with sleep onset. We implemented a method to track these fMRI activity maps in individuals performing a cognitive t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…If slow waves trigger specific occurrences of MW, other mechanisms could be responsible for the stability of these episodes 56 . Further investigations, including source localization or simultaneous recording of EEG and fMRI 57,58 , promise a deeper understanding of the mechanisms underlying these attentional lapses.…”
Section: -T-valuementioning
confidence: 99%
“…If slow waves trigger specific occurrences of MW, other mechanisms could be responsible for the stability of these episodes 56 . Further investigations, including source localization or simultaneous recording of EEG and fMRI 57,58 , promise a deeper understanding of the mechanisms underlying these attentional lapses.…”
Section: -T-valuementioning
confidence: 99%
“…Neuroimaging studies have shown that such differences between individuals may be explained by differences in task-related activation , functional connectivity (Wang et al, 2016;Yeo et al, 2015), dynamics and structural organization of the brain (Hawes et al, 2020;Poudel et al, 2018;Toppi et al, 2016…”
Section: Neural Basis Of Selective Vulnerability To Lapses Following Sleep Deprivationmentioning
confidence: 99%
“…For instance, network diffusion models (NDM) can emulate the pattern of pathological spread in the brain via white matter pathways, and have been useful in modelling the spread of disease in other neurological conditions such as Huntington’s and Alzheimer’s disease. 19-21 However, to date there has been no application of any mathematical model to assess and map the distribution of neurological events associated with COVID-19.…”
mentioning
confidence: 99%